2012
DOI: 10.1186/1472-6882-12-21
|View full text |Cite
|
Sign up to set email alerts
|

Daming capsule restores endothelial dysfunction induced by high-fat diet

Abstract: BackgroundDaming capsule (DMC), a traditional Chinese formula, has a lipid-modulating action with reduced adverse side effects as compared with other lipid lowering compounds. Since endothelial dysfunction often accompanies the hyperlipidemic state, we hypothesize that DMC might restore endothelial dysfunction produced by a high-fat (HF) diet. Importantly, we also investigate possible mechanisms involved in mediating the effects of DMC on vascular reactivity.MethodsRats were divided into four groups: control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Additionally, two proteins, NOS3 and IGF1, were present in the network. This is in-line with the protective effects of DMC against endothelial dysfunction of the aorta in high fat diet rats via upregulation of NOS3 expression [ 19 ] and the beneficial effects on diabetic symptoms [ 17 ]. Taken together, we hypothesized that DMC is a protective agent against CCI.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Additionally, two proteins, NOS3 and IGF1, were present in the network. This is in-line with the protective effects of DMC against endothelial dysfunction of the aorta in high fat diet rats via upregulation of NOS3 expression [ 19 ] and the beneficial effects on diabetic symptoms [ 17 ]. Taken together, we hypothesized that DMC is a protective agent against CCI.…”
Section: Discussionsupporting
confidence: 70%
“…Four proteins, p53, MMP1, MMP3, and MMP9, are involved in the networks. Moreover, DMC could abate myocardial cell inflammation [ 18 ] and reduce vascular endothelial injury [ 19 ]. Consistently, the related proteins, such as IL6, IL1B, TNF, ACE, EDN1, VEGFA, and ICAM1, could be seen in our networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, histological examination of H&E‐stained aortic sections from groups II and III showed that HFD resulted in extensive severe injury in the endothelial tissue through detachment of the endothelial layer and infiltration of the inflammatory cells. HFDs affect vascular function by causing impaired vascular responsiveness and elasticity (Zhang et al, ). Rats receiving the anti‐inflammatory diet (group IV) showed a nearly normal structure and the HFD‐fed rats that received celecoxib + ω‐3 PUFA (group VΙΙ) and ω‐3 PUFA and safranal (group VΙΙΙ) demonstrated an improvement in the endothelial layer compared with groups II and III.…”
Section: Discussionmentioning
confidence: 99%
“…Our previously randomized multicenter clinical trial has suggested that DMC exhibits an effective lipid‐lowering activity with low side effects . DMC can also improve heart function , reverse the impaired parasympathetic baroreflex in STZ‐induced diabetic rats with hyperlipidemia , and protect the endothelial dysfunction of aorta induced by high‐fat diet .…”
Section: Introductionmentioning
confidence: 99%